Testing and evaluation of web bearing capacity of corroded steel bridge girders. (1st July 2021) - Bao, Amanda; Guillaume, Caleb; Satter, Christopher; Moraes, Alana; Williams, Peter; Kelly, Tucker; Guo, Ying
Highlights: Testing of residual web bearing strength of corroded steel beams. Numerical modeling of web buckling behaviors of corroded steel girders. Developing quantitative relationship between corrosion condition and web bearing strength. Proposing steel girder web bearing strength reduction factor in bridge loading rating. Abstract: Aging bridges have become an important issue in the United States. One of the most dominant forms of deterioration for steel bridges is corrosion, which is typically due to moisture exposure and water leakage through deck joints. In cold regions, frequent use of deicing chemicals during the winter season further contributes to the corrosion process. Over the years, corrosion can become serious enough to disconnect the girder's web from its flanges. This excessive rust accumulation and metal area loss pose significant concerns for the reduction of the structural capacity of a girder, especially at its ends. In this paper, new corroded sample preparation and testing procedures were developed and implemented to study the residual web bearing capacity of corroded steel beam specimens in the lab. The laboratory testing results were used to extend the study to evaluate the residual web bearing capacity of corroded steel bridge girders. Corroded steel beam specimens were approximated in two forms in laboratory testing. In the first form, web thinning was achieved by prolonged submersion in bleach solution, to develop surface corrosion and section loss. In the second form, web holes were cut out of specimens with a plasma torch. Loading tests were performed on scaled steel beam specimens to investigate the consequent reduction in web bearing capacity due to web thinning and web area losses. The reaction at girder ends was simulated by a compression force exerted on the top flange of the steel beam specimens through a loading plate of the Material Testing System. The residual strengths of the steel beam specimens, varying in levels of corrosion, were analyzed and compared with the 3-D finite element modeling results. A quantitative relationship between corrosion condition and residual web bearing strength of I-plate steel girders is developed based on the laboratory testing and numerical modeling results. The findings in this study align with the observations from the real-world bridge practice. The proposed table of web bearing strength reduction factors can be used as a reference for evaluating residual web bearing capacity of corroded steel girders in bridge loading rating.